Secondary Multimodal Discourse of the Modern English Mass Culture as a Phenomenon of the Convergence Culture - Mariia Kuznetsova (Психолінгвістика)
The article focuses on psycholinguistic features of the secondary multimodal discourse of the modern English mass culture as a linguistic, social and cultural phenomenon and a specific type of communication with a peculiar context. This research paper represents the unique and valid definition of the secondary type discourse, its role, and place as the phenomenon of the convergence culture in the modern English youth subculture.